2015
DOI: 10.3389/fpsyg.2015.01776
|View full text |Cite
|
Sign up to set email alerts
|

Viewing Olfactory Affective Responses Through the Sniff Prism: Effect of Perceptual Dimensions and Age on Olfactomotor Responses to Odors

Abstract: Sniffing, which is the active sampling of olfactory information through the nasal cavity, is part of the olfactory percept. It is influenced by stimulus properties, affects how an odor is perceived, and is sufficient (without an odor being present) to activate the olfactory cortex. However, many aspects of the affective correlates of sniffing behavior remain unclear, in particular the modulation of volume and duration as a function of odor hedonics. The present study used a wide range of odorants with contrast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 33 publications
(56 reference statements)
1
2
0
Order By: Relevance
“…This is consistent with previous studies reporting women's stronger negative hedonic responses to odors of the axilla, of breath and of vaginal secretions (Doty et al, 1982(Doty et al, , 1978(Doty et al, , 1975Stevenson & Repacholi, 2003), but also males' desensitization to odors they are exposed to through their own body odors (Hummel et al, 2005). Olfactomotor measures were fully in line with the pleasantness ratings, since women also had shorter sniff durations than men in response to HMHA: indeed, sniff duration and odor pleasantness are usually negatively correlated (Ferdenzi et al, 2015b;Prescott et al, 2010). We cannot exclude that this sex difference in the perception of the odor could have reduced the hypothesized potential positive effect of facial attractiveness ratings of women.…”
Section: Discussionsupporting
confidence: 91%
“…This is consistent with previous studies reporting women's stronger negative hedonic responses to odors of the axilla, of breath and of vaginal secretions (Doty et al, 1982(Doty et al, , 1978(Doty et al, , 1975Stevenson & Repacholi, 2003), but also males' desensitization to odors they are exposed to through their own body odors (Hummel et al, 2005). Olfactomotor measures were fully in line with the pleasantness ratings, since women also had shorter sniff durations than men in response to HMHA: indeed, sniff duration and odor pleasantness are usually negatively correlated (Ferdenzi et al, 2015b;Prescott et al, 2010). We cannot exclude that this sex difference in the perception of the odor could have reduced the hypothesized potential positive effect of facial attractiveness ratings of women.…”
Section: Discussionsupporting
confidence: 91%
“…Though less studied than visual cues, responses to smells may be particularly important for gastrointestinal predictive processing. For example, parotid salivary secretion (the main component of appetitive salivary anticipation) depends upon exposure to olfactory signals [ 90 ], and olfactomotor responses to odors vary according to perceptions of pleasantness [ 91 ]. Hedonic ratings of food smells are associatively learned and depend upon the food- and hunger-related context [ 92 ].…”
Section: From Expectation To Ingestion To Digestion: a Predictive Pro...mentioning
confidence: 99%
“…However, like ourselves, these authors did not observe any difference between nostrils in ratings of pleasantness for any of the odours they used, though other authors have done so (Dijksterhuis et al, 2002;Herz et al, 1999). The presence and/or direction of any olfactory asymmetry may depend upon the extent to which an odour is familiar or unfamiliar (see Savic & Berglund, 2000) and possibly on the degree of pleasantness of the substance used (see Ferdenzi et al, 2015).…”
Section: Nostril Differences In the Effect Of Androstenol On Mood Scalesmentioning
confidence: 60%
“…Consequently, any change in duration, volume, airflow or number of sniffs might produce a change in perception of an odour (Mainland & Sobel, 2006, p. 183;Ferdenzi, Fournel, Thévenet, Coppin, & Bensafi, 2015). Our pilot work suggested that people do not spontaneously maintain a constant sniff over successive presentations of a stimulus (see Ferdenzi, Poncelet, Rouby, & Bensafi, 2014).…”
Section: Methodsmentioning
confidence: 89%